PENGARUH HASIL BELAJAR EKONOMI, LINGKUNGAN KELUARGA DAN TEMAN SEBAYA TERHADAP EFISIENSI DALAM BERKONSUMSI PADA SISWA KELAS X IPS SMA NEGERI 1 TUMPANG TAHUN AJARAN 2015/2016 - Rio Prasiska; Hari Wahyono; Yohanes Hadi Soesilo (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2017)
This research was conducted with the aim to describe the influence ofeconomic study result, family environment and colleague on efficiency toconsume student class X Social Science Senior High School 1 Tumpangduring 2015/2016 learning period. The research metodology used isquantitative descriptive with exsplanation format. The instrument used in thisresearch was tests and questionnaires. The number of respondents are 95students. The data were analyzed using SPSS 21 For Windows.Based on theanalysis of data obtained the following results : (1) there is influence betweeneconomic study result (X1) with efficiency to consume (Y) about 2,76%. (2)there is influence between family environment (X2) with efficiency to consume(Y) about 26,6643%. (3) there is influence between colleague (X3) withefficiency to consume (Y) about 7,8987%. DOI: https://dx.doi.org/10.17977/UM014v10i12017p083